Isaiah 1:2−3 and Isaiah 6: Isaiah ‘a prophet like Moses’ (Dt 18:18) - Alphonso Groenewald (HTS Teologiese Studies/Theological Studies, 2012)
The book of Isaiah is complex when one considers the reconstruction of the processes of its formation and transmission. If these complexities are examined more closely, it is apparent that there is a multiplicity of dimensions to the book. In order to discover the distinctive and unique characteristics of the book of Isaiah, we are forced to see the book within the wider context of other Hebrew literature. In this article, I examine one specific aspect of this book, namely some of the parallels that exist between the figure of Moses and its eponymous prophet. The deuteronomic depiction of Moses as the first prophet amidst the wilderness generation provided a major thematic force inspiring the redactors of the Book of Isaiah in their presentation of the prophet Isaiah. We get to know Isaiah as a prophet who, in his own historical context, continues the teachings of Moses, which enhances his authority. His words (Is 1:2−3) contain references to words spoken by Moses in Deuteronomy (Dt 32), and his call (Is 6) echoes that of Moses. The Torah of Moses is thus continued in the words and teaching of Isaiah.